Cognitive-Behavioral Therapy for Postbariatric Surgery Patients With Mental Disorders: A Pilot Study - Rudolph, Almut; Hilbert, Anja (Frontiers in Psychiatry, 2020)
Background Binge-eating disorder (BED) and major depressive disorder (MDD) following bariatric surgery are significant predictors for less post-operative weight loss and/or weight regain, however, cognitive-behavioral therapy (CBT) addressing these disorders following surgery has not been investigated so far. Objective This study examined feasibility of a short-term CBT based on evidence-based manuals for BED and MDD that were adapted to patients following bariatric surgery, and investigated its effectiveness in improving weight loss outcome, psychopathology, and psychosocial functioning. Materials and Methods In an uncontrolled proof-of-concept study, the CBT manual was piloted in N = 7 patients who had undergone roux-en-Y gastric bypass surgery at least 6 months before. Weight loss, eating disorder psychopathology, depressive symptoms, and self-esteem were assessed using clinical interviews and self-report questionnaires at pre-treatment, post-treatment, and in a 3-month follow-up. Results A significant reduction of body weight was found as well as medium to large effects in the improvement of eating disorder psychopathology, depressive symptoms, and self-esteem from pre-treatment to post-treatment were found. Most of those changes remained stable during the 3-month follow-up period. Study retention was 71.4%. Conclusions Feasibility and effectiveness of CBT were documented for patients with BED or MDD following bariatric surgery. Adaptations of the study procedure for proof-of-efficacy in randomized-controlled studies are discussed.